Foraging and feeding ecology of Platanista: an integrative review. (19th April 2018) - Kelkar, Nachiket; Dey, Subhasis; Deshpande, Kadambari; Choudhary, Sunil Kumar; Dey, Sushant; Morisaka, Tadamichi
Abstract: Limited visual perception in aquatic environments has driven the evolution of diverse sensory modalities in aquatic mammals. Dolphins largely use echolocation for prey capture in the face of limited visual and olfactory cues. Multiple foraging modes exist, although an understanding of how sensory systems are adapted to environmental and prey characteristics is limited. This is especially true for animals with extreme sensory specialisation, such as South Asian river dolphins of the genus Platanista . This taxon is effectively blind and retains plesiomorphic traits from its once‐diverse ancestors. Distributed in murky rivers of the Indus‐Ganga‐Brahmaputra basins, it is thought to use mainly echolocation for feeding on fish and shrimp. We hypothesised that foraging modes used by Platanista differ according to prey position in the water column (at the river surface, mid‐column, and bottom) and are mediated by ecomorphology, acoustics, prey characteristics, and habitat features. To test this, we combined a detailed review of the literature (anatomy–physiology–morphology studies, observations in captivity) with preliminary field observations and acoustics studies to investigate foraging mode selection. Platanista displays peculiar foraging and feeding behaviours, including side swimming, rotational feeding, and grasp‐suction feeding. Feeding is restricted to small prey with low body depth. At the river surface and bottom, echolocation‐based foraging may not be efficient due to acoustic reflection or reverberation effects. Platanista uses echolocation clicks to scan and detect prey at distances of about 20 m across the river mid‐column, possibly switching to passive listening at the surface, and electroreception at the bottom, to maximise prey capture rate and feeding success. Platanista is remarkable for its ability to persist in some of the most intensively used and abused river basins of the world. Using echolocation, electroreception, and passive listening might reduce overall foraging costs and contribute to the adaptability of the taxon.